PENGARUH MEDIA KARPET PUZZLE INOVATIF BERBASIS PERMAINAN ULAR TANGGA TERHADAP KEMAMPUAN LITERASI NUMERASI ANAK USIA DINI - Rizzatul Azzara; Mutia Afnida; Tisna Syafnita; Rakimahwati; Syahrul Ismet (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early childhood numeracy literacy skills play a crucial role as the foundation for logical thinking, problem-solving, and readiness for the next level of education. However, in practice, many children still struggle to recognize number concepts, connect symbols with quantities, and apply them in daily activities. This condition is exacerbated by the limited availability of learning media that can facilitate numeracy learning in an interactive and enjoyable manner, causing children to become easily bored and less motivated. This study aims to examine the effectiveness of a puzzle carpet based on the snakes and ladders game as an engaging alternative learning medium to enhance children’s numeracy literacy skills. This research employed a quantitative approach with a quasi-experimental design. The study population consisted of group B children at TK Telkom Padang, with purposive samples from class B6 (control) and class B8 (experimental), each comprising fewer than 15 children. Data collection techniques included observation, tests, and documentation. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing with SPSS 30.0 for Windows. The results showed an increase in the average score in the experimental class from 10.33 (pre-test) to 21.89 (post-test), while in the control class, scores increased from 9.56 to 20.06. A significance value of 0.001 (p < 0.05) indicated a significant effect. Thus, the puzzle carpet based on the snakes and ladders game was proven effective in improving early childhood numeracy literacy skills at TK Telkom Padang.